Length–weight relationships for 85 fish species from Guam. (27th August 2015) - Kamikawa, K. T.; Cruz, E.; Essington, T. E.; Hospital, J.; Brodziak, J. K. T.; Branch, T. A.
Summary: Length–weight relationships (LWRs) were developed for 85 reef and bottom‐fish species from Guam. These are the first published LWRs for Guam, and include new LWRs for nine species lacking these relationships in FishBase.